2013
DOI: 10.3109/13880209.2012.738333
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate (Punica granatum) peel extract provides protection against mercuric chloride-induced oxidative stress in Wistar strain rats

Abstract: The results clearly demonstrate that PPE treatment augments the antioxidant defense mechanism in mercuric chloride-induced oxidant toxicity. To the best of our knowledge this is the first report of the increase in erythrocyte PMRS activity in rats after supplementation with any kind of antioxidant supplementation. This study emphasizes the need for characterizing PPE for potential unknown antioxidant compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 26 publications
0
16
1
Order By: Relevance
“…40 The activity of PMRS has been shown to be elevated in erythrocytes of aged rats 19 and also in rats subjected to oxidative stress in vivo. 41 In view of the important role of erythrocyte PMRS in providing protection against oxidative stress during aging 39 and the hypothesis that the activity of PMRS may be an important determinant of animal life span, 42 the present observation of an increase in PMRS activity in senescent cells signifies increased oxidative stress. The increase in PMRS activity in senescent cells is more pronounced in old (24-month-old) rats, which again substantiates the higher oxidative stress in old rats.…”
Section: Figmentioning
confidence: 91%
“…40 The activity of PMRS has been shown to be elevated in erythrocytes of aged rats 19 and also in rats subjected to oxidative stress in vivo. 41 In view of the important role of erythrocyte PMRS in providing protection against oxidative stress during aging 39 and the hypothesis that the activity of PMRS may be an important determinant of animal life span, 42 the present observation of an increase in PMRS activity in senescent cells signifies increased oxidative stress. The increase in PMRS activity in senescent cells is more pronounced in old (24-month-old) rats, which again substantiates the higher oxidative stress in old rats.…”
Section: Figmentioning
confidence: 91%
“…Previous studies have demonstrated that heavy metals increase the generation of ROS causing damage to macromolecules, membrane ion transport systems, enzymes, lipid peroxidation in hematological system leading probably to genotoxic effects on blood (Kumar et al 2013;Ashour & El-Shemi 2014) in rats treated by mercury chloride and cadmium, respectively. Barium, an alkaline earth metal, alters hematological parameters including the decrease in blood hemoglobin content and thrombocytes count in industrial workers (Tarasenko et al 1977), while its genotoxicity has not been previously characterised in experimental models.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to Pb is related to cancer, neurotoxicity, hepatotoxicity, and cardiovascular disorder (Kumar et al, 2013). The method by which NAC and DMSA ameliorated Pb and HgCl 2 toxicity is not examined well till now.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, antioxidants, plant extracts and chelating agents have the potential to inhibit these effects (Kumar et al, 2013;Jarrar, 2003;Mehana et al, 2012;Ekor et al, 2010). Our findings showed that both NAC and DMSA ameliorated the decrease in serum and mRNA expression of antioxidants.…”
Section: Discussionmentioning
confidence: 99%